The measurement of meaning - an exercise in field semantics - Botha, Phil J. (Journal for semitics, 1989)
The eight words for Torah in Psalm 119 are presented in this article as an example of a lexical field. The associative environment of each of the eight words are compared with one another by reducing the psalm to kernel sentences and quantifying information about subject, object, modus, etc., of the verbs used in connection with each of the Torah words. The relative distances between points representing the words in the semantic space are computed by using the generalised distance formula of solid geometry. The results of this attempt at spatial differentiation between and representation of Torah words in Psalm 119 are also discussed.